Positive long-term effects of year-round horse grazing in orchid-rich dry calcareous grasslands–Results of a 12-year study - Köhler, Martina; Schmidt, Annika; Hölzel, Norbert; Baasch, Annett; Tischew, Sabine (Frontiers in Ecology and Evolution, 2023)
Dry calcareous grasslands are among the most species-rich habitats worldwide but strongly endangered by abandonment causing a severe decline of characteristic species such as orchids. To counteract further degradation, economically sustainable restoration tools such as megaherbivore grazing, that aim to substitute extinct wild grazers, should be considered. However, the long-term effects on target species of dry grasslands, and in particular for orchid populations, is still unclear. To contribute to this knowledge gap, we applied vegetation surveys (5 m × 5 m), as well as large-scale census-based orchid observation and mapping of habitat structures (50 m × 50 m) in a year-round grazing scheme of a Natura 2000 site in Central Germany over twelve years. The horses and their grazing activity were observed via GPS telemetry. We fitted linear mixed models to evaluate whether Ophrys apifera density was affected by horse feeding frequency, habitat structure variables (bare soil patches, woody plant cover), grassland type or years. The main results were that the target dry calcareous grassland vegetation significantly increased in species numbers and cover. The total abundance of O. apifera increased from 1,237 (2013) and 1,893 (2018), to 4,652 (2021) individuals. O. apifera density was positively affected by horse feeding frequency as well as grazing-induced enhanced bare soil patches but underlying mechanisms varied between the three classified grassland types. Our results indicate that low-intensity year-round horse grazing as a relatively new restoration tool in dry calcareous grasslands has the potential to enhance floristic biodiversity in general, and particularly O. apifera density in the long run. Furthermore, we showed that high-value xeric grasslands with outstanding orchid abundances can be integrated into the year-round grazing system and that there is no need of fencing off such sections.